Analysing engineering students' information retrieval behaviour using online databases as information sources - Prananda Navitas; Yusnita Febrianti (Jurnal Kajian Informasi dan Perpustakaan, 2022)
Students at the tertiary education level need the information to complete their assignments at the university. Information retrieval behavior among university students is interesting to study because it shows the ability of search techniques and the diversity of information needed. The researcher has extensively researched information-seeking behavior at this level of education. However, more needs to be explicitly performed on the information retrieval process conducted by engineering students. The purpose of the present study was to reveal engineering students' information retrieval behavior process when using information sources from online database websites through analysis the types of online database websites the students used as primary information sources, why the students used these websites, and identified the challenges in information seeking using online database websites. For this study, data were collected using an internet-based questionnaire distributed among students at the Department of Urban and Regional Planning, ITS. The study results indicated that engineering students used search engines as the primary information source due to their richness and flexibility. In this case, we have found additional results regarding the patterns of presentation and the interactivity necessary to optimize the function of online database websites. Also, the study has found the challenges faced by students in retrieving information and how they overcome the situation by using different keywords.